Hypoxic culture of human pluripotent stem cell lines is permissible using mouse embryonic fibroblasts. (September 2012) - Badger, Jennifer L; Byrne, Meg L; Veraitch, Farlan S; Mason, Chris; Wall, Ivan B; Caldwell, Maeve A
Aim: Hypoxia is used within in vitro stem cell culture to recreate conditions similar to the in vivo environment surrounding the early blastocyst, from which embryonic stem cells can be isolated. Traditionally, basic research has used a coculture feeder system to culture pluripotent stem cells; however, it is possible that lowered oxygen may restrict cellular metabolic activity of the inactivated mouse embryonic fibroblasts (iMEFs) by disrupting oxygen-dependent pathways, such as ATP production through aerobic respiration. In this work, we examined the potential to continue using routine culture methods, such as iMEFs, to support human pluripotent cell expansion under hypoxia instead of feeder-free methods that can cause cell instability and offer a poor cell attachment rate.Materials & methods: Metabolic activity and viability studies were carried out in normoxic and hypoxic conditions. Pluripotent stem cells were introduced into hypoxia on iMEFs and the rate of colony expansion was compared with normoxic conditions. In addition, pluripotent stem cells were grown in hypoxia for over 6 months to demonstrate maintenance of pluripotency. Immunocytochemistry and western blotting evaluated the activity of the hypoxic transcription factor, HIF1A.Results: Hypoxia does not significantly affect viability or metabolic activity of feeder cells, and there is no detrimental effect on the rate of pluripotent stem cell colony expansion when cells are cultured in hypoxia. In addition, hypoxic pluripotent stem cells maintain their pluripotent nature and ability to differentiate into the three germ layers.Conclusion: The traditional iMEF coculture method is suitable for use in hypoxia and does not need to be replaced with feeder-free systems for hypoxic culture of human pluripotent stem cell lines in basic research.